Pembaharuan Kajian Sifat Fisik Lapisan Acrotelm dan Catotelm Beberapa Tutupan Lahan Gambut Pedalaman di Kalimantan Tengah - Bachtiar Sitinjak; Nina Yulianti; Zafrullah Damanik; Fengky F. Adji (LPPM Universitas Palangka Raya, 2022)
The purpose of this research was to determine the profile and physical properties of the soil layers of acrotelm and catotelm on 4 (four) inland peatland covers. This research was conducted in June – August 2021. Each research site was assigned 3 plots of minipeat for each land cover namely natural forest, secondary forest, repeat and degraded forest. The research location is in the Laboratory of Natural Peat Forest (LAHG) Sebangau and Special Purpose Forest Area (KHDTK) Tumbang Nusa. Peat samples were analyzed in the Laboratory of UPT LLG-CIMTROP and Laboratory of Agronomy Department, University of Palangka Raya. The data were analyzed using descriptive analysis. The results showed that the physical properties at the KHDTK Tumbang Nusa has an average level of hemic and sapric maturity with dark reddish brown and very dusky red; the average bulk density was 0.19 g cm-3 of the acrotelm and 0.16 g cm-3 of the catotelm; water content of 418.49% of acrotelm and 595.78% of catotelm; the porosity of the acrotelm is 73.64% and 76.92% of the catotelm; fiber content of acrotelm 24.18% and 16.49% of catotelm. The research location of LAHG Sebangau has an average level of hemic and sapric maturity with reddish black color; the average bulk density was 0.11 g cm-3 of the acrotelm and 0.12 g cm-3 of the catotelm; water content 577,23% of acrotelm and 665,36% of catotelm ; porosity of 81.51% of acrotelm and 83.08% of catotelm; fiber content 37.87% of acrotelm and 25.60% of catotelm.